2018
DOI: 10.1007/s10067-018-4147-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultrasound-guided corticosteroid injection compared to oxygen–ozone (O2–O3) injection in patients with knee osteoarthritis: a randomized controlled trial

Abstract: Osteoarthritis (OA) is a chronic multifactorial disease characterized by progressive joint degeneration. The purpose of this study was to compare the effects of ultrasound-guided corticosteroid injection with oxygen-ozone injection in patients with knee OA. This double-blind randomized clinical trial was performed on 62 patients with knee OA. The patients were randomly divided into two groups. In the first group 40 mg triamcinolone (1 cc) and in the second group 10 cc (15 μg/ml) oxygen-ozone (O-O) were injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 27 publications
2
42
0
1
Order By: Relevance
“…Flow diagrams depicting the patient selection process were reported only in 4 papers. 13,14,19,20 Finally, we found that 3 trials were prospectively registered in a public clinical trial registry, 13,14,16 one was registered retrospectively, 19 whereas the others did not mention any registration, which should be mandatory according to the Consolidated Standards of Reporting Trials 2010 guidelines.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Flow diagrams depicting the patient selection process were reported only in 4 papers. 13,14,19,20 Finally, we found that 3 trials were prospectively registered in a public clinical trial registry, 13,14,16 one was registered retrospectively, 19 whereas the others did not mention any registration, which should be mandatory according to the Consolidated Standards of Reporting Trials 2010 guidelines.…”
Section: Resultsmentioning
confidence: 91%
“…A detailed description of each study has been provided in Table 1. 8,[13][14][15][16][17][18][19][20][21][22] Study Design and Quality All studies were, as per inclusion criteria, RCTs. The study designs were highly variable: patients in the control groups received different injection or treatment, such as HA in 3 studies; corticosteroids in 4 studies; and placebo, hypertonic dextrose, radiofrequency, or celecoxib þ glucosamine in the remaining 4 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A nivel articular, y especialmente en la gonalgia por artrosis de rodilla, también se han publicado artículos que consolidan el uso del ozono mostrando su eficacia versus placebo, plasma rico en plaquetas, ácido hialurónico y corticoides (15)(16)(17)(18); asimismo, una revisión sistemática remarca esa eficacia en el metanálisis obtenido (19). En este número de la Revista de la Sociedad Española del Dolor se presenta un interesante e innovador artículo de Fernández-Cuadros ME y cols., sobre la repercusión del tratamiento con ozono en la gonartrosis, no solo sobre parámetros clínicos de eficacia, sino también, y por primera vez en la literatura científica, sobre indicadores bioquímicos y radiológicos.…”
unclassified